Electrochemical Evaluation of Corrosion Inhibiting Layers Formed in a Defect from Lithium-Leaching Organic Coatings. Issue 7 (2nd June 2017) - Visser, Peter; Meeusen, Mats; Gonzalez-Garcia, Yaiza; Terryn, Herman; Mol, Johannes M. C.
Abstract : This work presents the electrochemical evaluation of protective layers generated in a coating defect from lithium-leaching organic coatings on AA2024-T3 aluminum alloys as a function of neutral salt spray exposure time. Electrochemical impedance spectroscopy was used to study the electrochemical properties on a macroscopic scale. An electrochemical model allowed to quantitatively link the electrochemical behavior with the physical model of the layer in the damaged area as studied by scanning electron microscopy. Local potentiodynamic polarization curves obtained from micro-cell measurements showed an increase of the passive range in the defect area due to the formation of a robust protective layer. Scanning vibrating electrode technique measurements confirmed the non-reversible long-term corrosion protection of these generated layers in the coating defect.